Anemia, iron status, and associated protective and risk factors among children and adolescents aged 3 to 19 years old from four First Nations communities in Quebec - Tahir, Emad; Lemire, Mélanie; Lucas, Michel; Little, Matthew; Anassour-Laouan Sidi, Elhadji; Mergler, Donna; Bélanger, Richard E.; Ayotte, Pierre; Gros-Louis McHugh, Nancy (Canadian Journal of Public Health, 2020)
Objectives: Anemia and iron deficiency (ID) are frequent among Indigenous children of Canada, but few data are available in Quebec. The present study aimed to characterize anemia and ID prevalence and associated protective and risk factors among First Nations youth in Quebec. Methods: The 2015 First Nations (JES!-YEH!) pilot study was conducted among children and adolescents (3 to 19 years; n=198) from four First Nations communities in Quebec. Blood and urine samples and anthropometric measurements were collected. Hemoglobin (Hb), serum ferritin (SF), plasma hs-CRP, and urinary cotinine levels were measured. Factors associated with anemia and ID (including traditional and market food consumption) were assessed using an interview-administered food frequency questionnaire, based on which nutritional intakes were calculated. Structural equation models were used totest associations. Results: The prevalence of anemia and ID was elevated (16.8% and 20.5% respectively). Traditional meat, fruit, and fruit juice (naturaland powdered)—via their positive association with vitamin C intake—were the only food variables positively associated with SF (coefficient [95% CI] 0.017 [0.000, 0.114]; 0.090 [0.027, 0.161]; and 0.237 [0.060, 0.411]). Male sex was also associated with higher SF (0.295 [0.093, 0.502]). Inflammation status (hs-CRP > 5 mg/L) was inversely associated with Hb (−0.015 [−0.025,−0.005]), whereas SF was positively associated with Hb (0.066 [0.040, 0.096]). Fruit and juice consumption was also positively associated with Hb, via vitamin C intake and SF (0.004 [0.001, 0.010]; 0.008 [0.003, 0.017]). Conclusions: Interventions fostering healthier food environments as well as higher consumption of traditional meats and foods naturally rich in vitamin C, which is known to enhance iron absorption, and fighting inflammation could contribute to decrease the high prevalence of anemia and ID in this young Indigenous population. Objectifs : L’anémie et la carence en fer sont fréquentes chez les enfants autochtones au ...